[001]-oriented LiMn0.6Fe0.4PO4/C nanorod microspheres contributing high-rate performance to olivine-structured cathode for lithium-ion battery. (December 2022) - Zhang, Baichao; Meng, Wu; Gong, Yifan; Hu, Guorong; Peng, Zhongdong; Du, Ke; Makuza, Brian; Wu, Jiahui; Xie, Xiaoming; Cao, Yanbing
Abstract: Recently, cathode materials for Li-ion batteries (LIBs) with high-voltage platforms have become a research hotspot. Olivine-structured LiMnPO4 has the advantage of 4.1 V voltage platform but also has been plagued by poor e - /Li +  conductivity. Here, we report a facile synthetic strategy to fabricate LiMn0.6 Fe0.4 PO4 /C (LMFP) composite. Such composite is composed of [001]-oriented nanorods and assembled into dense microspheres. The [001]-oriented nanorod structure exhibits a shortened Li + diffusion length resulting from a smaller dimensional size in the [010] direction. Meanwhile, the conductive carbon nanolayer is uniformly coated on the surface of LiMn0.6 Fe0.4 PO4 nanorods, which greatly improves the e - conductivity of the material. The [001]-oriented structure feature combined with improved e - conductivity contributes to the delivery of extraordinary rate capabilities (141.6 mAh/g at 10C) and remarkable cycling stabilities (97.8% retention rate after 300 cycles at 1C). Such rational-designed nanorod microspheres are good candidates for the next generation of olivine-structured cathode for high-rate, high-energy, and high-safety LIBs. Graphical abstract: Synopsis: The conformal carbon layer coating design combined with [001]-oriented nanostructure synergistically enhances LMFP performance and breaks through the limitation of poor e - /Li + conductivity of LMFP. Image 1 Highlights: An ultrathin carbon layer (∼3 nm) was successfully constructed on the surface of LMFP nanorods. The prepared [001]-oriented LMFP has a shortened Li + diffusion length (∼30 nm) in bulk. The coating design combined with [001]-oriented structure synergistically enhances LMFP performance. The [001]-oriented LMFP exhibits extraordinary rate capabilities and remarkable cycling durability. The synthesis process is eco-friendly and provides opportunities for scaling up.